Cryopreservation of papaya seeds cv. Sukma, Callina, and Caliso: Effect of loading treatment and immersion time in plant vitrification solution-2 - FITRI FATMA WARDANI; DARDA EFENDI; DINY DINARTI; Joko Ridho Witono (Smujo International, 2019)
Abstract. Wardani FF, Efendi D, Dinarti D, Witono JR. 2019. Cryopreservation of papaya seeds cv. Sukma, Callina, and Caliso: Effect of loading treatment and immersion time in plant vitrification solution-2. Nusantara Bioscience 11: 71-78. Sukma, Callina, and Caliso are papaya cultivars released by the Center for Tropical Horticulture Studies, IPB University, Bogor, West Java, Indonesia. In general, papaya seeds cannot be stored for a long time with a conventional GenBank storage system, even though some of them consider as “orthodox” class of seed. Cryopreservation, storage at an ultra-low temperature (-196 0C) of liquid nitrogen, could be possible for long-term storage of papaya seeds. The experiment conducted to get the necessary of loading treatment and the best immersion time in PVS2 for cryopreservation of papaya seeds cv. Sukma, Callina, and Caliso, so they still had considerable viability. We conducted experiment as factorial in completely randomized design, with the first factor was loading treatment with two levels (with and without loading treatment), and the second factor was immersion time in PVS2 with three levels (15, 30 and 45 min). So, there was six treatment and we used 50 seeds for each treatment. Results showed that the three papaya cultivars gave different responses to the treatment before cryopreservation proved that papayas seed had different characteristics, depending on genotype. For papaya seeds cv. Sukma, loading treatment was not needed and the best immersion time in PVS2 was 15 min. The viability of papaya seeds cv. Callina was low, so we should try another treatment before cryopreservation. For papaya seeds cv. Caliso, loading treatment was needed and the best immersion time in PVS2 was 30 min.